Catastrophe and Redemption : The Political Thought of Giorgio Agamben - Whyte, Jessica (Jessica Stephanie) (Book collections on Project MUSE., 2013)
"A striking new reading of Agamben's political thought and its implications for political action in the present"--Provided by publisher